2004
DOI: 10.1679/aohc.67.31
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional architecture of elastin and collagen fiber networks in the human and rat lung

Abstract: Collagen and elastin fibers are the major components of the lung connective tissue, but their spatial organization has not been well documented. We have demonstrated the three-dimensional architecture of collagen and elastin fiber networks in the human and rat lung using scanning electron microscopy. These networks in their original forms were extracted by an alkali-water maceration technique and a formic acid treatment, respectively. The collagen fibers formed a continuum extending throughout the lung and ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 11 publications
5
87
0
3
Order By: Relevance
“…Collagen and elastic tissue fibers, proteoglycans, and other glycoproteins are the main structural macromolecules of the connective tissue elements of mammalian lung (Hance & Crystal, 1975;Hopkins et al 1986;Crouch et al 1997;Tochima et al 2004). More recent studies report that collagen fibers fail at strains between 6 and 22% (Liao & Belkoff, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Collagen and elastic tissue fibers, proteoglycans, and other glycoproteins are the main structural macromolecules of the connective tissue elements of mammalian lung (Hance & Crystal, 1975;Hopkins et al 1986;Crouch et al 1997;Tochima et al 2004). More recent studies report that collagen fibers fail at strains between 6 and 22% (Liao & Belkoff, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Arising from the need to exploit and integrate their distinctly different mechanical properties, in animal tissues, elastic tissue fibers are almost constantly found in close topographical relationship to the collagenous fibers (Elden, 1968;Gosline, 1976;Gosline & French, 1979;Alter, 2004). In the compliant mammalian lung, elastic tissue occurs abundantly and diffusely (Gonçalves et al 1995;Tochima et al 2004). Carton et al (1964) observed that more elastic tissue was present in the lungs of two mammalian species than was theoretically expected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A reduction in the tensile strength of these tendons was also observed. In the mature human lung, elastin constitutes approximately 30% of the dry tissue weight [9]; elastic elements form a complex, three-dimensional fibrous network, interwoven with collagenous elements, and there is evidence of mechanical connections between the two [65]. In a guinea pig model, the effect of enzymatically removing elastin on the quasi-static mechanical properties of lung parenchymal strips was to cause a large reduction in initial modulus and an increase in extensibility [75].…”
Section: Functionmentioning
confidence: 99%